The subversive potential and position of mass media during the Arab Spring – the case of Tunisia, Egypt and Syria - Stojanović, Lazar (Sociološki pregled, 2025)
A series of demonstrations in the territory of Arab countries is labelled with the phrase “Arab Spring”. The mass character of the civic gathering and the final epilogue were greatly influenced by the means of mass communication, with the dominant position of social networks. At the root of the conflict were social problems in this part of the world and deeply entrenched regimes with large amounts of power. The ultimate goal of this form of civil disobedience was directed towards changes in government. The paper focuses on the countries where the coup occurred, Tunisia and Egypt, but also Syria, as a country with significant unrest and a harsh reaction by the security forces, analyzing the context of the emergence of the unrest, the course of events and the final epilogue.